2014
DOI: 10.1371/journal.pone.0103490
|View full text |Cite
|
Sign up to set email alerts
|

Serum Nutritional Biomarkers and Their Associations with Sleep among US Adults in Recent National Surveys

Abstract: BackgroundThe associations between nutritional biomarkers and measures of sleep quantity and quality remain unclear.MethodsCross-sectional data from the National Health and Nutrition Examination Surveys (NHANES) 2005–2006 were used. We selected 2,459 adults aged 20–85, with complete data on key variables. Five sleep measures were constructed as primary outcomes: (A) Sleep duration; (B) Sleep disorder; (C) Three factors obtained from factor analysis of 15 items and labeled as “Poor sleep-related daytime dysfunc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
75
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(85 citation statements)
references
References 72 publications
5
75
5
Order By: Relevance
“…The NDNS results showed SS having lower levels of plasma fruit and vegetable biomarkers compared with RS whereas this study only found lower levels of plasma vitamin C however, biomarker data (n = 145) was low compared to the number of participants with 4 day diaries (n = 12,159) and may be the reason of why no other associations were found between sleep duration and biomarkers. These results were supported by Beydoun et al among US adults however, sleep measures were the outcomes (Beydoun et al 2014). When SS (5-6 h) were compared to normal sleepers (7-8 h), total carotenoid concentration was linked to increased risk of short sleep.…”
Section: Discussionsupporting
confidence: 63%
“…The NDNS results showed SS having lower levels of plasma fruit and vegetable biomarkers compared with RS whereas this study only found lower levels of plasma vitamin C however, biomarker data (n = 145) was low compared to the number of participants with 4 day diaries (n = 12,159) and may be the reason of why no other associations were found between sleep duration and biomarkers. These results were supported by Beydoun et al among US adults however, sleep measures were the outcomes (Beydoun et al 2014). When SS (5-6 h) were compared to normal sleepers (7-8 h), total carotenoid concentration was linked to increased risk of short sleep.…”
Section: Discussionsupporting
confidence: 63%
“…Conversely, even if the consumption of other vitamins and minerals was not deficient in terms of recommendations for basic intake, the intake differences between men with and without sleep disorder point towards potential associations between micronutrient intake and sleep. According to recent studies, lower intakes of vitamin C and potassium were associated, respectively, with non‐restorative sleep and sleepiness (Grandner et al ., ) and lower serum folate concentration was related independently to sleep disturbance (Beydoun et al ., ). Similar results are also demonstrated in our study, while the underlying mechanisms remain unclear.…”
Section: Discussionmentioning
confidence: 97%
“…Of note, 35.9% reported <7 h (4.6% < 5 h; 31.2% 5–6 h), 56.4% reported 7–8 h and 7.7% reported >8 h of sleep. As previously described [42], we considered multiple NHANES questions for generating sleep quality indices. An exploratory factor analytic approach was used on 21 items from NHANES that were measured on a four-point or five-point Likert scale with higher scores reflecting worse sleep quality (Appendix A).…”
Section: Methodsmentioning
confidence: 99%